2021
DOI: 10.18488/journal.61.2021.91.201.219
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Mobile Learning Systems Adoption in Zimbabwe Rural Secondary Schools

Abstract: Contribution/Originality:This study show is one of the first to examine the likelihood of adopting or deferring the adoption of MBLs in Zimbabwe's rural secondary schools. Therefore, it contributes to the existing literature on factors that contribute to the adoption of MBLs using unified theory of acceptance and use of technology (UTAUT). INTRODUCTIONIn today's technologically-driven educational landscape, most schools are augmenting traditional teaching and learning processes by adopting mobile based learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Based on this, it can be inferred that, when teachers understand the ease of use of tablets in their classroom, they will practise and develop skills and knowledge of teaching with technology. This finding concurs with the literature that the ease of use of a system influences the probability of adopting mobile devices in secondary schools (Muzurura et al, 2021;Papadakis et al, 2021c). This study contributes to the existing body of knowledge that the acceptance of technology is valuable as teachers develop their skill in teaching with tablet devices with ease and little effort.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on this, it can be inferred that, when teachers understand the ease of use of tablets in their classroom, they will practise and develop skills and knowledge of teaching with technology. This finding concurs with the literature that the ease of use of a system influences the probability of adopting mobile devices in secondary schools (Muzurura et al, 2021;Papadakis et al, 2021c). This study contributes to the existing body of knowledge that the acceptance of technology is valuable as teachers develop their skill in teaching with tablet devices with ease and little effort.…”
Section: Discussionsupporting
confidence: 90%
“…Today's technologically steered educational institutions like universities and schools, are moving away from traditional teaching and learning processes by adopting a mobile learning system. This system has created the platform for educational ecosystems where teachers and students network using internet-enabled mobile devices, such as netbooks, tablets, laptops, and smartphones for teaching and learning (Gamage & Perera, 2021;Muzurura et al, 2021). In the study to assess Spanish university teachers' implementing of mobile learning in their teaching practices, the findings showed that teachers' perceptions of teaching with mobile devices modelled good teaching practice that transforms teaching practice in the classrooms (Romero-Rodríguez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%